Observer-based single phase robustness load frequency sliding mode controller for multi-area interconnected power systems - Nguyen, Cong-Trang; Trong Hien, Chiem; Phan, Van-Duc (Bulletin of Electrical Engineering and Informatics, 2024)
In multi-area interconnected power systems (MAIPS), all the plant state’s measurement is stiff due to the lack of a device or the cost of the sensor is expensive. To solve this restriction, a novel sliding mode control technique- based load frequency controller (LFC) is investigated for MAIPS where the estimation states of the system is utilized fully in the switching surface and controller. Initially, a single-phase switching function is suggested to dismiss the reaching phase in traditional sliding mode control (TSMC) approach. Secondly, the MAIPS’s unmeasurable variables is estimated by using the suggested observer tool. Next, a new single phase robustness load frequency sliding mode controller (SPRLFSMC) for the MAIPS is established based on the support of the observer instrument and output data only. The entire plant’s stability is ensured through the Lyapunov theory. Even though the plant’s variables are not measured, the obtained results in the simulation display that the frequency remains in the nominal domain under load instabilities on the MAIPS. The simulation results for a three-area interconnected electricity plant verify the preeminence of the anticipated SPRLFSMC over other current controllers with respect to settling time and overshoot.